Factors underlying migratory timing of a seasonally migrating bird - Taylor J. Bobowski; Christen Bossu; Rafael Rueda-Hernández; Teia Schweizer; Ingrid Tello-Lopez; Thomas B. Smith; Richard Feldman; Emily Cohen; Kristen Ruegg (Scientific Reports)
Abstract Bird migration has fascinated natural historians and scientists for centuries. While the timing of migration is known to vary by species, population, sex, and individual, identifying the cause of this variation can be challenging. Here we investigate factors underlying migratory timing in a long-distance migratory bird, the Common Yellowthroat (Geothlypas trichas), using a population genomic approach. We begin by creating a map of genetic variation across geographic space (a “genoscape”) using lcWGS from across the breeding range. We then utilize genetic assays to assign 249 wintering and 1050 northward migrating birds to genetically distinct breeding populations. Additionally, we estimate the expected spring onset date in each predicted breeding region and calculate the remaining migratory distance for northward migrating birds. Our findings indicate that when population genetic structure is not a factor in the analysis, it appears that birds captured early in the season are migrating to breeding grounds where spring arrives later, which contrasts with prior research. However, when we incorporate population structure into our analysis, our results align with predictions, indicating that birds captured earlier in the season are indeed heading to breeding grounds where spring arrives earlier. Further analysis revealed that the disparity between results obtained with and without population genetic structure can be attributed to the fact that individuals from the western genetic group migrate three times the distance to the west, despite breeding at the same latitude. Our findings suggest that categorizing large numbers of migrating birds into genetically distinct groups can reveal population-specific patterns in migratory timing and shed light on the relative contributions of different selective forces responsible for the observed patterns.